Evaluation model for knowledge sharing in information security professional virtual community / Alireza Tamjidyamcholo - Tamjidyamcholo, Alireza (2014)
Cyberspace communities can be considered as a warehouse of knowledge that provides people with an opportunity to receive or share information. The most important challenge for knowledge sharing among information security professionals is motivating participation in knowledge sharing. Many professional virtual communities (PVC) have failed due to reasons, such as the low willingness of members to share knowledge with others. This research proposes two models to evaluate and understand the determinants of knowledge sharing behavior in PVCs. In the first model, nine hypotheses have been examined while five hypotheses have been examined in the second model. First model analyses key factors, consist of attitude, self-efficacy, trust, norm of reciprocity, and shared language, with respect to the information security workers’ intention to share knowledge. Information security professionals in virtual communities, including the Information Security Professional Association (ISPA), Information Systems Security Association (ISSA), Society of Information Risk Analysts (SIRA), and LinkedIn security groups, were surveyed to test the proposed model. Confirmatory factor analysis (CFA) and the structural equation modelling (SEM) technique were used to analyse the data and evaluate the research model. The results show that the research model fit the data well and the structural model suggests a strong relationship between attitude, trust, and norms of reciprocity to knowledge sharing intention. Hypotheses regarding the influence of self-efficacy and reciprocity, to knowledge sharing attitude were upheld. Shared language did not influence either the attitude or intention to share knowledge. The second model is composed of two main parts. The first part is the Triandis theory, which is adapted to analyse the other determinants of knowledge sharing behavior in PVCs. The second part explores the quantitative relationship between knowledge sharing and security risk reduction. One hundred and forty-two members from the LinkedIn information security groups participated in this study. PLS analysis shows that perceived consequences, affect, and facilitating conditions have significant effects on knowledge sharing behavior. In contrast, social factors have shown insignificant effects on knowledge sharing behavior. The results of the study demonstrate that there is a positive and strong relationship between knowledge sharing behavior and information security risk reduction.